Perception of the risk of adverse reactions to analgesics: differences between medical students and residents - Castillo Guzmán, Sandra; González Santiago, Omar; Delgado Leal, Ismael A.; Lozano Luévano, Gerardo Emmanuel; Reyes Rodríguez, Misael J.; Elizondo Solis, César Vidal; Nava Obregón, Teresa Adriana; Palacios Ríos, Dionicio (2016)
Background. Medications are not exempt from adverse drug reactions (ADR) and how the physician perceives the risk of prescription drugs could influence their availability to report ADR and their prescription behavior. Methods. We assess the perception of risk and the perception of ADR associated with COX2-Inbitors, paracetamol, NSAIDs, and morphine in medical students and residents of northeast of Mexico. Results. The analgesic with the highest risk perception in both group of students was morphine, while the drug with the least risk perceived was paracetamol. Addiction and gastrointestinal bleeding were the ADR with the highest score for morphine and NSAIDs respectively. Discussion. Our findings show that medical students give higher risk scores than residents toward risk due to analgesics. Continuing training and informing physicians about ADRs is necessary since the lack of training is known to induce inadequate use of drugs.